Outage probability analysis of maritime FSO links - Ata, Yalçın; Alouini, Mohamed-Slim (Frontiers in Communications and Networks, 2023)
In this paper, the outage performance of maritime free-space optical(FSO) communication system is analyzed and a new maritime FSO link configuration is presented. Channel model for maritime FSO link includes the combined effect of turbulence, pointing error, angle-of-arrival (AOA) fluctuations, and attenuation. While maritime turbulence channel is modeled by Lognormal distribution, pointing error and AOA fluctuations are assumed to be Beckmann and Rayleigh distributed, respectively. Turbulence power spectrum is considered to present the Kolmogorov characteristics and Rytov variance of a propagating Gaussian beam in maritime environment is obtained. The probability density function (PDF), cumulative distribution function (CDF) and outage probability of maritime communication channel are obtained analytically. Outage performance of a maritime communication link is given depending on various parameters of the maritime environment, the Gaussian beam, and the (FSO) communication system.